Shariah Compliance Status, Market Conditions dan IPO Oversubscription - Ramadani Lalu Ahmad (The Indonesia Capital Market Institute, 2021)
This study aims to examine the effect of Shariah Compliance Status, Market Conditions on IPO Oversubscription. The sample in this study is a company that conducts an Initial Public Offering (IPO) in the period 2017-2020, using Probability Sampling as a sample determinant and analyzed using multiple linear regression. The results of this study indicate that Shariah Compliance Status and Market Conditions have a significant effect with values ​​of 0.045 and 0.021 on IPO Oversubscription. The result is due to the better understanding of Muslim investors. Meanwhile, in the position of market conditions, with economic pressure due to the Covid-19 pandemic, it creates astigma wait-and-seeon investors because the pandemic creates higher speculation and risk.